Increased Levels of Human Carotid Lesion Linoleic Acid Hydroperoxide in Symptomatic and Asymptomatic Patients Is Inversely Correlated with Serum HDL and Paraoxonase 1 Activity. (29th May 2012) - Cohen, Elad; Aviram, Michael; Khatib, Soliman; Rabin, Asaf; Mannheim, Dalit; Karmeli, Ron; Vaya, Jacob
Abstract : Human carotid plaque components interact directly with circulating blood elements and thus they might affect each other. We determined plaque paraoxonase1 (PON1) hydrolytic-catalytic activity and compared plaque and blood levels of lipids, HDL, PON1, and HbA1c, as well as plaque-oxidized lipids in symptomatic and asymptomatic patients. Human carotid plaques were obtained from symptomatic and asymptomatic patients undergoing routine endarterectomy, and the lesions were ground and extracted for PON activity and lipid content determinations. Plaque PONs preserved paraoxonase, arylesterase, and lactonase activities. The PON1-specific inhibitor 2-hydroxyquinoline almost completely inhibited paraoxonase and lactonase activities, while only moderately inhibiting arylesterase activity. Oxysterol and triglyceride levels in plaques from symptomatic and asymptomatic patients did not differ significantly, but plaques from symptomatic patients had significantly higher (135%) linoleic acid hydroperoxide (LA-13OOH) levels. Their serum PON1 activity, cholesterol and triglyceride levels did not differ significantly, but symptomatic patients had significantly lower (28%) serum HDL levels and higher (18%) HbA1c levels. Thus LA-13OOH, a major atherogenic plaque element, showed significant negative correlations with serum PON1 activity and HDL levels, and a positive correlation with the prodiabetic atherogenic HbA1c. Plaque PON1 retains its activity and may decrease plaque atherogenicity by reducing specific oxidized lipids (e.g., LA-13OOH). The inverse correlation between plaque LA-13OOH level and serum HDL level and PON1 activity suggests a role for serum HDL and PON1 in LA-13OOH accumulation.